America’s Most Successful Export to Japan: Continuous Improvement Prog rams - Dean M., Schroeder; Robinson, Alan G. (MIT Sloan Management Review, 1991)
CONTINUOUS IMPROVEMENT Programs (CIPs) unleash employee experience and I creativity to improve both products and processes. They are often c ited as the most important difference between the Japanese and Western management styles and as a major factor in Japan’s economic success.2 Yet the CIP was conceived, developed, and brought to maturation in the United States. After World War II, the U.S. government helped to expo rt it to Japan, where it was well received and promptly flourished. De spite the long history and well-documented benefits of such systems, f ew U.S. companies have invested effort in CIPs equivalent to that of t heir Japanese competitors. Japanese companies have put almost forty ye ars into the development and refinement of CIPs, or kaizen programs as they are known in Japan, and have brought the art and science of mana ging them to new levels of sophistication. The aim of these programs i s precisely to design and implement a system whose natural equilibrium is constant improvement and change. How can a company that does not h ave such a program compete with one that does? In this paper we give t he historical background of CIPs, which we believe is essential for a useful understanding of these programs. We document their export acros s the Pacific immediately following World War II and illustrate their power as a competitive weapon when fully and properly deployed. We the n identify and discuss requirements for successful implementation and suggest reasons why many U.S. firms find them difficult to start and m aintain. We conclude by arguing that what is commonly perceived to be the “best practice” of CIP management is itself open to improvement. T hroughout the article, we identify promising directions for companies to pursue so that all minds in the company, not just those of a few at the top, are actively solving problems, reducing costs, and eliminati ng waste.